Culturally Adaptive Religious Leadership and Islamic Education Development in Muslim Minority Communities from Eastern Indonesia - Fitrah Fauziah; Muhaemin Muhaemin; Fatmaridah Sabani (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Religious leaders occupy a pivotal role in sustaining Islamic education within remote, heterogeneous Muslim minority communities, yet their specific mechanisms remain undertheorized. This study investigated the roles of religious leaders in strengthening Islamic education through cultural integration in Buyasuri District, Lembata, East Nusa Tenggara, Indonesia, alongside its socio-cultural implications. Employing a descriptive qualitative design, this study selected 15 participants across three villages via purposive sampling, including religious, educational, and community figures. Data were gathered through semi-structured interviews, participant observation, and document analysis over a three-month period. Analysis followed the Miles–Huberman–Saldaña interactive model, ensuring trustworthiness through triangulation and member checking. The findings revealed that religious leaders execute four interrelated roles—educator, mentor, motivator, and moral exemplar—across formal and nonformal settings. Cultural integration is enacted by embedding Islamic teachings within indigenous Kedang linguistic conventions, ceremonies, and communal gatherings. This culturally adaptive approach significantly enhances community participation, social solidarity, and religious engagement. Principal enablers include high community trust and institutional legitimacy, whereas structural deficits and geographical remoteness present major barriers. Ultimately, this study proposes a conceptual model linking religious leadership, cultural integration, value internalization, and community empowerment, advancing the theoretical understanding of religiously embedded education in multicultural contexts.